THE IMPORTANCE OF WEB MATERIALS IN LEARNING FOREIGN LANGUAGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the growing significance of web-based materials in the process of learning foreign languages. It highlights how online resources—such as interactive websites, digital dictionaries, language learning platforms, video tutorials, forums, and mobile applications—enhance language acquisition through accessibility, real-time interaction, and diverse multimedia content. The article also discusses the motivational impact of web materials and their role in fostering independent and personalized learning. The integration of technology into language education is shown to increase learner engagement and improve practical language skills in listening, speaking, reading, and writing.